Sistem-sistem Epistemologi Humanisme Ekologis (Studi Tafsir al-Mishbah) - Syefriyeni Syefriyeni (Intizar, 2015)
The result of research that examines the concept of ecological humanism in the interpretation of al-Mishbah. This is interesting because this paper discusses the more specific context of environmental philosophy in the perspective of al-Misbah interpretation. This commentary was written by M. Quraish Shihab. The concept of ethical nature of the environment starts from controversial thought between traditional humanism and ecological humanism. Ecological humanism actually conveys the thought that humans should be responsible for the natural environment as it should not be depleted. In brief, the epistemology systems in the interpretation of al-Mishbah show a strong system built and fused among scientific concepts, penalties, and values built on the foundation of faith and strong belief. Thus, the faith and belief are not separated from the nature. Then the damage of nature gets the punishment from God in the context of maintaining the nature closely related to the values of faith and worship.